Assessment of knowledge, attitude and practice of pharmacovigilance among people working in community pharmacy: a cross-sectional study at Banke District in Nepal - Chaudhary, Aswani; Gupta, Arvind Kumar; KC, Balaram; Sah, Niraj Prasad; Sarraf, Deependra Prasad (Nepal Medical College Journal, 2022)
The burden of ADRs is high globally and it accounts for considerable morbidity, mortality, and extra cost to the patients. Pharmacovigilance plays a significant role in the detection, assessment, understanding and reporting of ADRs. Objective of the study was to assess the knowledge, attitude and practice of pharmacovigilance among people working in community pharmacies in the Banke District. A prospective cross-sectional descriptive study was conducted among people working in community pharmacies in Banke district from February to March 2022 using a 20 item semi-structured questionnaire. Ethical approval was obtained from the institutional ethical review committee (501/078-079). Data were entered in Microsoft Office Excel 2010 and descriptive statistics like mean, frequency, percentage and standard deviation were calculated. Data were analyzed using SPSS-22 and data were presented as tables. Only 46 (22.89%) respondents knew the definition of pharmacovigilance. Mean knowledge score of the respondents was 2.87±2.05 out of the maximum possible score of 10. Only 40 (19.9%) respondents had knowledge score ≥50%. Out of 201, 180 (89.55%) respondents thought that reporting of adverse drug reaction will be beneficial in the future. A total of 136 (67.66%) respondents had positive attitude towards pharmacovigilance. One hundred and seventy seven (88.06%) had not seen ADR reporting form. A total of 166 (82.59%) respondents had poor practice towards pharmacovigilance. Majority of the respondents had poor knowledge, positive attitude and poor practice of pharmacovigilance. There is urgent need of educational programs on pharmacovigilance to raise awareness.